Increase resource power electronics module on the physics of failure method; MATEC Web of Conferences; Vol. 19 : The 2nd International Youth Forum “Smart Grids”, Tomsk, Russia, October 6-10, 2014 - Kravchenko E. V. Evgeny Vladimirovich (2014, 2014)
Title screen